Effectiveness of Existing Organs for Fighting Unethical Conduct of Leaders in Promoting Good Governance in Local Goverment Authorities (LGAS): A Case of Kinonodoni Municipality - Dar es Salaam, Tanzania - Tarimo, Valentino Baloshi; Mallya, Emmanuel; Ngware, Suleman (dialektika kontemporer, 2025)
Aiming to promote good governance among public leaders, Tanzania instituted the Public Leadership Code of Ethics Act No. 13 of 1995. This legislation sought to promote ethical conduct through established organs tasked with combating unethical behaviour. However, persistent leadership scandals—such as corruption and fraud, particularly within local government authorities—have raised public and governmental concern, as documented in media reports, literature, and official government publications. These ongoing issues call into question the efficacy of the organs established to ensure ethical conduct among public leaders. This study, therefore, examined public perceptions of the effectiveness of these organs in promoting good governance within the Local Government Authorities (LGAs) of Kinondoni Municipality, Dar es Salaam, Tanzania. Adopting a qualitative case study design, the study focused on the Ethics Secretariat, the Prevention and Combating of Corruption Bureau (PCCB), the Judiciary, and the Police. A total of 85 participants, including local government leaders and citizens, were selected via convenience and purposive sampling. Data were collected through interviews, focus group discussions, and document reviews. The findings indicate that the selected organs are perceived as ineffective in combating leaders' unethical conduct due to institutional corruption, nepotism, and dishonesty. Other impediments to their effectiveness include political interference, inadequate staffing and resources, and poor working environments. The study recommends that the central government, particularly the Ministry of Regional Administration and Local Government, undertake a comprehensive restructuring of these organs to ensure their effective operation. Furthermore, it recommends improving working conditions and ensuring the timely remuneration of staff within these institutions.